MENINGKATKAN MOTORIK KASAR ANAK MELALUI PERMAINAN TRADISIONAL GOBAK SODOR - Aushafil Karimah; Siti Nur Aini Menia Siti Nur Aini Menia (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Universitas Ibrahimy, 2021)
Children's gross motor development can be developed through the traditional game of gobak sodor.The formulation ofthe problem in thisresearch is howthe process ofimplementing gobak sodor playing activitiesinimproving gross motor skills of early childhood, how to increase children's gross motor skills through traditionalgames of gobak sodor, and howthe results ofimplementing gobak sodor playing activitiesin improving gross motorskillsof early childhoodingroupBatMutiaraSemiringMangaranKindergartenSitubondo.ThetypeofresearchusedisClassroom Action Research (CAR) by solving learning problemsin class, problem solving is done in a cycle. Eachcycle consists of planning, action, observation, and reflection with the aim of improving the quaty of learning in theclassroom. Based on observationalresearch,it can be seen thatthe results ofthe implementation oftheGobak Sodorgame to improve the gross motor development of children in MutiaraKindergarten include; Firstthe teacher dividesthe groups, each group consists of 4-5 children.The resultsshowed an increase in aspects of children's gross motordevelopmentthroughtheGobakSodorgame, namelyPre-cycle,thepercentage value reached39%. asfortheaverageachievement ofthe child indicators are 4.4. afterthe action of Cycle I,the percentage value reached 61%. While theaverage achievement of the indicators achieved by children are 5.2 and the Cycle II action, the percentage valuereaches 83%.The average value ofthe child'sindicators of achievementis: 5.9 it has been found a comparison ofthelevelofgrossmotordevelopmentof childrenshowsthatchildrenhaveincreasedtheirgrossmotordevelopment.